Angiographic catheter with hydrophilic lubricating coating and application
A hydrophilic lubricating coating and segmented structure for angiography catheters address the challenges of friction and thrombosis, enhancing insertion accuracy and safety.
Patent Information
- Application Number
- CN202411327096.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-18
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional angiography catheters face challenges with high surface friction and hydrophobicity, leading to difficult insertion, potential tissue damage, and increased risk of thrombosis due to platelet and hemoglobin adsorption.
A hydrophilic lubricating coating is applied to the angiography catheter, reducing friction and adsorption of small molecules, and a segmented structure with varying hardness and flexibility is implemented to facilitate precise insertion and minimize vascular injury.
The hydrophilic coating significantly reduces surface friction and thrombosis risk, enabling faster and more accurate catheter placement with reduced patient injury and improved treatment efficacy.
Smart Images

Figure CN119185663A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical device technology, specifically to an angiography catheter with a hydrophilic lubricating coating and its application. Background Technology
[0002] Peripheral vascular disease is primarily caused by arteriosclerosis, where fatty plaques accumulate on the inner walls of arteries, obstructing blood flow. This condition is often associated with risk factors such as high blood pressure, high cholesterol, diabetes, and smoking. Its harms include reduced blood flow to the lower limbs, potentially causing intermittent claudication, pain, numbness, and in severe cases, slow wound healing or ulceration. Uncontrolled peripheral vascular disease can also increase the risk of heart disease and stroke.
[0003] Currently, the professional technology for treating peripheral vascular diseases in my country is developing rapidly. Traditional surgical techniques are constantly being improved, and new treatment methods—interventional therapy—are being used more and more widely in clinical practice. In the clinical diagnosis of peripheral vascular diseases, the surgeon selects a specific-shaped angiography catheter based on the geometric characteristics of the target area. Guided by a guidewire, the catheter is inserted into the target vessel through a vein or artery, and then contrast agent is injected to produce an angiographic effect, thus achieving the diagnosis of the disease. Diagnostic angiography catheters can be divided into selective and non-selective angiography catheters. Among them, commonly used non-selective angiography catheters include multi-port pigtail angiography catheters and multi-port straight-tip angiography catheters, with a maximum flow rate of 20-25 ml / s. Selective angiography catheters come in different shapes depending on the location of use. For example, catheters commonly used for the arteries above the aortic arch include Headhunter type I, II, and III, and Simmon type I, II, and III; for the renal arteries and veins, there are RDC type catheters and Simmon type I, II, and III catheters; and for the iliac arteries and veins, there are Cobra type I, II, and III catheters and SHK type catheters. Most selective angiography catheters do not have side holes, and their maximum flow rate can reach 7-8 ml / s.
[0004] However, whether selective or non-selective angiography catheters, insertion into the target vessel via a vein or artery requires precise manipulation of the catheter's twisting and bending, followed by retraction and adjustment to ensure insertion. This procedure is technically challenging, cumbersome, time-consuming, and prone to causing injury to the patient. Furthermore, the hydrophobic nature of the catheter's outer surface easily attracts platelets and hemoglobin, leading to thrombosis and endangering the patient's health. Therefore, it is necessary to improve and integrate both the catheter and its coating to obtain a superior, improved hydrophilic lubricated angiography catheter, as well as a method for fabricating such a catheter.
[0005] In view of this, the present invention is hereby proposed. Summary of the Invention
[0006] Therefore, in order to address the problems of high surface friction coefficient and poor hydrophobicity of traditional contrast catheters, it is necessary to improve and integrate both the catheter and the coating to obtain a higher-performance, improved hydrophilic lubricated contrast catheter, as well as a method for preparing such a hydrophilic lubricated contrast catheter.
[0007] The angiography catheter of this invention has a hydrophilic lubricating surface coating. When the catheter contacts human tissue, its surface lubrication reduces damage caused by friction with the tissue and allows doctors to more accurately and quickly insert the catheter into the correct blood vessel branch. Its hydrophilicity also reduces the adsorption of small molecules such as platelets and hemoglobin, thereby preventing thrombus formation within the patient's blood vessels.
[0008] This invention overcomes the problem of friction between the angiography catheter and the blood vessel wall, causing damage to surrounding tissues, during angiography procedures due to the long operation time required for the doctor to adjust the position of the angiography catheter to enter the correct branch. Furthermore, it shortens the time doctors spend performing angiography with the assistance of medical imaging equipment, which is beneficial for the doctor's health. At the same time, this invention overcomes the problem of angiography catheters easily causing vascular thrombosis in the body, thus improving the treatment effect of cardiovascular diseases and protecting the patient's health.
[0009] One of the objectives of this invention is to provide an angiography catheter with a hydrophilic lubricating coating.
[0010] The contrast catheter with a hydrophilic lubricating coating includes a catheter seat, a tube body, a transition section, and a tip. One end of the tube body is connected to the catheter seat, and the inner cavity of the tube body is in communication with the inner cavity of the catheter seat. The other end is connected to the transition section, and the other end of the transition section is connected to the tip. The tube body, transition section, and tip are all externally covered with the hydrophilic lubricating coating.
[0011] In a preferred embodiment of the present invention,
[0012] The catheter seat has a hollow structure with a catheter seat inlet and a catheter seat outlet. The catheter seat inlet communicates with the outside, and the tube body and the catheter seat are connected through the catheter seat outlet. There are two blades perpendicular to the outer surface of the catheter seat on opposite sides of the catheter seat. The blades on the side facilitate the rotation of the catheter seat.
[0013] The tube body includes an inner tube body layer, a middle braided layer, and an outer tube body layer;
[0014] The transition section includes an inner layer and an outer layer; the layered structure of the tube body and the transition section gives the angiography catheter good support, torsion control, elasticity and bending resistance.
[0015] The hardness of the tube body, transition section and head end decreases sequentially;
[0016] The Shore hardness of the outer layer of the tube is 40-70D;
[0017] The outer layer of the transition section has a Shore hardness of 25–40D.
[0018] The Shore hardness of the outer layer at the head end is 25-40D;
[0019] A contrast ring is added to the tip of the catheter to facilitate positioning of the catheter tip during the angiography procedure;
[0020] In a preferred embodiment of the present invention,
[0021] The catheter seat is manufactured by extrusion or injection molding;
[0022] The tube body is made by extrusion and braiding processes; preferably, the inner tube is first extruded using an extruder, then stainless steel wires are cross-braided onto the outer surface of the inner tube using a braiding machine, and finally the outer tube is extruded using an extruder.
[0023] The transition section is made by extrusion and braiding processes; preferably, the inner tube is first extruded using an extruder, then stainless steel wires are cross-braided onto the outer surface of the inner tube using a braiding machine, and finally the outer tube is extruded using an extruder.
[0024] The head end is manufactured using an extrusion molding process or a 3D printing process; preferably, the head end is extruded using an extruder and a developing ring is installed using specialized equipment.
[0025] The tube body and the conduit seat are connected by bonding, injection molding or welding; the tube body, transition section and head end are connected by welding, injection molding or bonding.
[0026] In a preferred embodiment of the present invention,
[0027] The conduit seat is made of acrylonitrile-butadiene-styrene terpolymer (ABS) or nylon 12;
[0028] The inner layer of the tube is made of polytetrafluoroethylene (PTFE), nylon 12, or block polyetheramide elastomer (PEBAX); the block polyetheramide elastomer is preferably at least one of PEBAX7233 SA01, PEBAX6333 SA01, PEBAX5533 SA01, PEBAX4533 SA01, and PEBAXMV 1074 SA01; wherein PTFE meets the requirements of high temperature resistance, corrosion resistance, low coefficient of friction, low adhesion, and non-toxicity, which is conducive to the smooth passage of the angiography guidewire;
[0029] The middle braided layer of the tube is made of stainless steel; preferably it is made of 10 to 30 stainless steel round or flat wires with a braiding density of 50 to 80 PPI; the stainless steel is medical grade stainless steel, preferably SUS304 or SUS316 (medical grade).
[0030] The outer layer of the tube is made of at least one of block polyetheramide elastomer (PEBAX), nylon, thermoplastic polyurethane polyimide, styrene-based thermoplastic elastomer, acrylonitrile-butadiene-styrene terpolymer, and thermoplastic silicone elastomer; the block polyetheramide elastomer is preferably at least one of PEBAX7233SA01, PEBAX7033 SA01, PEBAX6333 SA01, PEBAX5533SA01, PEBAX4533 SA01, and PEBAXMV1074 SA01; the nylon is preferably nylon 12;
[0031] The inner layer of the transition section is made of polytetrafluoroethylene (PTFE), nylon 12 or block polyether amide elastomer (PEBAX) material; the block polyether amide elastomer is preferably at least one of PEBAX MV1074 SA01, PEBAX 4033SA01 and PEBAX3533SA01;
[0032] The outer layer of the transition section is made of at least one of block polyether amide elastomer (PEBAX), nylon, thermoplastic polyurethane, polyimide, styrene-based thermoplastic elastomer, acrylonitrile-butadiene-styrene terpolymer, and thermoplastic silicone elastomer; the block polyether amide elastomer is preferably at least one of PEBAX 4533SA01, PEBAX MV1074 SA01, PEBAX4033SA01, and PEBAX 3533SA01; the nylon is preferably nylon 12;
[0033] The intermediate braided layer of the transition section is made of stainless steel; preferably, it is made of 10 to 30 stainless steel round or flat wires with a braiding density (PPI) of 70 to 100 PPI; the stainless steel is medical grade stainless steel, preferably SUS304 or SUS316 (medical grade); stainless steel round wires are preferred, as they provide a small surface area for support and give the transition section excellent flexibility and elasticity.
[0034] The head end is made of polytetrafluoroethylene (PTFE), nylon 12 or block polyether amide elastomer (PEBAX) material; the block polyether amide elastomer is preferably at least one of PEBAX MV1074 SA01, PEBAX 4033SA01 and PEBAX 3533SA01;
[0035] The material of the head end imaging ring is preferably at least one of platinum-iridium alloy, tantalum alloy, and rubber; most preferably, it is platinum-iridium alloy.
[0036] The hydrophilic lubricating coating is covalently bonded to the catheter surface, thus firmly and tightly coating the surface of the angiography catheter.
[0037] The hydrophilic lubricating coating is polymerized by free radical polymerization or other polymerization methods. The monomer is preferably at least one of acrylamide, N-vinylpyrrolidone, and hydroxyethyl methacrylate; the initiator is at least one of I-2959, ammonium persulfate, and LAP photoinitiator; and the grafting agent that bonds to the surface of the conduit substrate is preferably at least one of benzophenone, ammonium persulfate, and waterborne polycarbodiimide crosslinking agent.
[0038] The hydrophilic lubricating coating is firmly bonded to the catheter surface by surface grafting. First, the catheter is placed in an acetone or isopropanol solution containing at least one of benzophenone, ammonium persulfate, and aqueous polycarbodiimide crosslinking agent for swelling, with a swelling time of 1-60 minutes. After swelling, the catheter is removed, cleaned with isopropanol and deionized water, and dried under nitrogen. The monomer and initiator are dissolved in deionized water to obtain a pre-impregnation solution. The swollen catheter is immersed in the pre-impregnation solution for 1-10 minutes, then slowly removed and irradiated under ultraviolet light for 1-10 minutes. This process is repeated several times. Then, residual monomers are washed away with a large amount of deionized water and dried under nitrogen to obtain the contrast catheter with the hydrophilic lubricating coating.
[0039] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, preferred embodiments are described below in detail with reference to the accompanying drawings. Attached Figure Description
[0040] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0041] Figure 1 A schematic diagram of an angiography catheter structure with photo-controlled deformation;
[0042] 1. Catheter base, 2. Catheter body, 3. Transition section, 4. Head end, 5. Imaging ring, 6. Hydrophilic lubricating coating;
[0043] Figure 2 This is a schematic diagram of the cross-section of the A-A' tube.
[0044] 7. Outer layer of tube; 8. Inner layer of tube; 9. Intermediate braided layer of tube;
[0045] Figure 3 This is a schematic diagram of the cross-section of the B-B' transition layer;
[0046] 10. Outer layer of transition section; 11. Inner layer of transition section;
[0047] Figure 4 This is a schematic diagram of the side view of the guide head;
[0048] 12. Guide head end tube body, 13. Imaging ring. Detailed Implementation
[0049] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0050] All raw materials used in the examples are commercially available; PEBAX 5533SA01, PEBAX 4033SA01, PEBAX2533SA01, PEBAX 7033SA01, PEBAX 3533SA01, PEBAX 6333SA01, PEBAX 7233SA01, and Nylon 12 are manufactured by Arkema, France.
[0051] The thermoplastic polyurethane (TPU) is manufactured by BASF in Germany.
[0052] The manufacturer of styrene-based thermoplastic elastomers (TPES) is Kraton S.p.A., Inc.
[0053] Hydrophilicity test method: Use a water contact angle tester and test according to GB / T 30693-2014 standard.
[0054] Lubricity testing method: A universal tensile testing machine is used to clamp the catheter with silicone clamps to simulate the internal environment of human tissue and perform tensile testing to calculate the coefficient of friction.
[0055] like Figure 1As shown, the contrast catheter with hydrophilic lubricating coating of the present invention includes a catheter seat 1, a tube body 2, a transition section 3, a guide tip end 4, a contrast ring 5, and a hydrophilic lubricating coating 6. One end of the tube body 2 is connected to the catheter seat 1, and the inner cavity of the tube body is connected to the inner cavity of the catheter seat. The other end is connected to the transition section 3, and the other end of the transition section 3 is connected to the guide tip end 4.
[0056] like Figure 2 As shown, the tube body 2 includes an outer tube body 7, a middle braided layer 9, and an inner tube body 8;
[0057] like Figure 3 As shown, the structure of transition section 3 includes an outer layer 10 and an inner layer 11.
[0058] like Figure 4 As shown, the structure of the guide head includes a guide head tube 12 and a developing ring 13.
[0059] Example 1
[0060] The conduit seat has a hollow structure with openings at the front and back. There are two flaps on the side of the conduit seat perpendicular to the outer surface of the conduit seat. The conduit seat is made of acrylonitrile-butadiene-styrene terpolymer material by injection molding. The tube body includes an inner tube body, a middle braided layer and an outer tube body.
[0061] The inner layer of the tube is made of polytetrafluoroethylene, the middle braided layer of the tube is made of 16 304 stainless steel flat wires with a braiding density of 60 PPI, and the outer layer of the tube is made of PEBAX 7233SA01. The tube is made by extrusion and braiding process. First, the inner tube is extruded by an extruder, then the stainless steel wires are cross-braided on the outer surface of the inner tube by a braiding machine, and then the outer tube is extruded by another extruder.
[0062] The transition section consists of an inner layer and an outer layer. The inner layer is made of polytetrafluoroethylene (PTFE), and the outer layer is made of PEBAX 5533SA01. Both the inner and outer layers are produced by extrusion.
[0063] The guide head is integrally molded and made of PEBAX 4033SA01. The tube body is directly extruded using an extrusion process, and then a imaging ring is installed onto the guide head using a platinum ring machine.
[0064] The hardness of the tube body, transition section, and guide tip decreases sequentially: the outer layer of the tube body has a hardness of 60D, the outer layer of the transition section has a hardness of 50D, and the guide tip has a hardness of 30D. The tube body is welded to the guide seat; the tube body, transition section, and guide tip are also welded together.
[0065] The test conditions were a dry air environment at 25℃. The water contact angle of the conduit sample surface was observed to be approximately 78° using a water contact angle tester. The surface friction coefficient of the conduit was calculated to be 0.24 after testing on a tensile testing machine.
[0066] In a New Zealand white rabbit vein implantation experiment, the amount of thrombus generated in each sample was 0.0159±0.0074g.
[0067] Example 2
[0068] The difference between Example 2 and Example 1 is:
[0069] After obtaining the catheter sample according to the method described in Example 1, it was cleaned, dried, and then proceeded to the next step to prepare a hydrophilic lubricating coating.
[0070] First, the catheter was immersed in an acetone solution of benzophenone for swelling for 30 minutes. After swelling, it was removed, rinsed with isopropanol and deionized water, and dried under nitrogen. The monomer acrylamide and initiator I-2959 were dissolved in deionized water to obtain a coating monomer solution. The swollen catheter was immersed in the coating monomer solution for 5 minutes, followed by in-situ irradiation under ultraviolet light for 5 minutes. Then, residual monomer was washed away with a large amount of deionized water and dried under nitrogen to obtain the contrast catheter with a hydrophilic lubricating coating.
[0071] The test conditions were a dry air environment at 25℃. The water contact angle of the conduit sample surface was observed to be approximately 32° using a water contact angle tester. The surface friction coefficient of the conduit was calculated to be 0.10 after testing on a tensile testing machine.
[0072] Example 3
[0073] The difference between Example 3 and Example 1 is:
[0074] After obtaining the catheter sample according to the method described in Example 1, it was cleaned, dried, and then proceeded to the next step to prepare a hydrophilic lubricating coating.
[0075] First, the catheter was immersed in an acetone solution of benzophenone for swelling for 30 minutes. After swelling, it was removed, rinsed with isopropanol and deionized water, and dried under nitrogen. The monomer acrylamide and initiator I-2959 were dissolved in deionized water to obtain a pre-impregnation solution. The swollen catheter was immersed in the pre-impregnation solution for 5 minutes, then slowly removed and irradiated under ultraviolet light for 5 minutes. This process was repeated several times. Then, residual monomers were washed away with a large amount of deionized water and dried under nitrogen to obtain the contrast catheter with a hydrophilic lubricating coating.
[0076] The testing conditions were a dry air environment at 25℃. The water contact angle of the catheter sample surface was observed to be approximately 16° using a water contact angle tester. The surface friction coefficient of the catheter was calculated to be 0.05 after testing on a tensile testing machine. In a New Zealand white rabbit vein implantation experiment, the amount of thrombus generated per sample was 0.0073 ± 0.0050 g.
[0077] Example 4
[0078] The difference between Example 4 and Example 3 is as follows:
[0079] The aforementioned steps are the same as in Example 2. After the catheter swells, the monomer N-vinylpyrrolidone and initiator I-2959 are dissolved in deionized water to obtain a pre-impregnation solution. The swollen catheter is immersed in the pre-impregnation solution for 5 minutes, then slowly removed and irradiated under a UV lamp for 5 minutes. This process is repeated several times. Then, a large amount of deionized water is used to wash away the residual monomer and the catheter is dried under nitrogen to obtain the contrast catheter with the hydrophilic lubricating coating.
[0080] Apart from the differences mentioned above, the other structures of Example 3 are the same as those of Example 2.
[0081] The test conditions were a dry air environment at 25℃. The water contact angle of the conduit sample surface was observed to be approximately 25° using a water contact angle tester. The surface friction coefficient of the conduit was calculated to be 0.08 after testing on a tensile testing machine.
[0082] Comparative Example 1
[0083] Chinese invention patent CN 105983138 A, entitled "A hydrophilic lubricating polyurethane medical interventional catheter and its preparation method".
[0084] The catheter body is made of a molten mixture of carboxyl-containing thermoplastic polyurethane elastomer and carboxyl-free thermoplastic polyurethane elastomer. The outer surface of the catheter is coated with a hydrophilic coating that can form covalent bonds with the catheter. The hydrophilic coating includes a bottom layer coating that can be grafted onto the outer surface of the catheter, and a top layer coating that forms a semi-interpenetrating cross-linked network structure with the bottom layer coating.
[0085] Comparative Example 2
[0086] Chinese invention patent CN 105983139 A, entitled "A method for preparing a hydrophilic lubricating coating on the surface of a medical interventional catheter".
[0087] This method relates to a method for preparing a hydrophilic lubricating coating on the surface of a medical interventional catheter. The catheter surface is subjected to plasma treatment and grafted with acrylic acid to make the surface contain active carboxyl groups. Then, a two-layer coating system is constructed to form a multi-component cross-linked structure in which a polyisocyanate curing agent acts as a cross-linking agent connecting the carboxyl groups on the catheter surface, the polyurethane in the coating, and the hydrophilic polymer polymethyl vinyl ether-maleic anhydride, so that the bottom of the coating is covalently connected to the catheter and tightly bonded to the top of the coating.
[0088] In existing technologies, to graft a strong coating onto the surface of the catheter, elastomeric materials containing surface groups are typically incorporated during the extrusion process of the elastomeric catheter, as in Comparative Example 1; or the surface of the finished catheter is plasma-modified to obtain elastomeric materials containing surface groups, as in Comparative Example 2. This approach has certain drawbacks. First, the resulting coating is relatively thick and difficult to control. Second, the raw materials are complex, and monomer residues are easily left on the catheter surface, potentially causing some toxicity to humans. Third, the process is relatively complex and difficult to apply in production.
[0089] In stark contrast to the surface modification methods of Comparative Examples 1-2, Examples 2-4 employ a chemical grafting method to establish a strong chemical bond between the catheter substrate surface and the hydrogel coating. Based on this principle, the hydrogel coating has the characteristics of lower thickness, better hydrophilicity and lubricity, and simpler processing.
[0090] The hydrophilicity and lubricity of the hydrogel hydrophilic lubricating coatings in Examples 2-4 were tested. It was observed that the water contact angle decreased by approximately 75% compared to the uncoated angiography catheter, and the coefficient of friction decreased by more than 75%. Compared to the surface treatment methods in Comparative Examples 1-2, both the water contact angle and coefficient of friction were optimized. Furthermore, the treatment methods in Examples 2-4 were less time-consuming, requiring only approximately 30-60 minutes, and used relatively common monomer raw materials. This represents a significant advantage compared to the more than 24 hours required for Comparative Examples 1-2.
[0091] Furthermore, the segmented structure of embodiments 1-4 ensures that the catheter body has a certain degree of rigidity, providing excellent propulsion performance. The transition section has a certain degree of flexibility and elastic recovery ability, preventing bending when entering the corresponding vascular branch. The soft guide tip has a certain degree of flexibility, avoiding damage to surrounding tissues during propulsion. The medical-grade PEBAX material used in this invention preferably has a low coefficient of friction, and the product surface is designed with a hydrophilic lubricating coating, which can reduce damage to the human body during use. The stable melt flow of PEBAX material gives it excellent processing performance, enabling a smooth transition from the soft section to the hard section of the catheter, meeting the requirements of different segments of the angiography catheter in terms of hardness and elasticity. The stainless steel braided mesh used in the braided layer provides good support and torsion control performance. The inner layer preferably uses PTFE material, which meets the requirements of high temperature resistance, corrosion resistance, low coefficient of friction, low adhesion, and non-toxicity.
[0092] Therefore, Examples 1-4 describe a coating technology for angiography catheters used in angiography procedures. This catheter significantly reduces its surface friction coefficient and greatly improves its surface hydrophilicity, thereby reducing patient injury and thrombus formation during the procedure. It is an angiography catheter with a simple manufacturing process and excellent performance, featuring a hydrophilic lubricating coating.
[0093] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the invention should be included within the scope of protection of the invention. It should be noted that similar reference numerals and letters in the following figures denote similar items; therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
Claims
1. An angiographic catheter having a hydrophilic lubricating coating, characterized in that: The angiography catheter with a hydrophilic lubricating coating comprises a catheter seat, a tube body, a transition section, a guide tip and a hydrophilic lubricating coating on the surface; One end of the tube body is connected to the catheter seat, the inner cavity of the tube body is connected to the inner cavity of the catheter seat, the other end is connected to the transition section, the other end of the transition section is connected to the guide head end, and the entire surface of the catheter has a hydrophilic lubricating coating; The hydrophilic lubricating coating is prepared from raw materials including hydrophilic hydrogel material and chemical grafting agent.
2. The angiographic catheter with a hydrophilic lubricating coating as claimed in claim 1, characterized in that : The hydrophilic lubricating coating material monomer is at least one of acrylamide, N-vinyl pyrrolidone, and hydroxyethyl methacrylate; and / or, The polymerization method is at least one of free radical polymerization and emulsion polymerization.
3. The angiographic catheter with a hydrophilic lubricating coating as claimed in claim 1, characterized in that : The hydrophilic lubricating coating material initiator is at least one of I-2959, ammonium persulfate, and LAP photoinitiator; and / or, The grafting agent bonded to the surface of the catheter substrate is preferably at least one of benzophenone, ammonium persulfate, and an aqueous polycarbodiimide crosslinking agent.
4. The angiographic catheter with a hydrophilic lubricating coating as claimed in claim 1, characterized in that : The mass ratio of the monomer to the initiator of the hydrophilic lubricating hydrogel coating is 1:(0.05-100); preferably 1:(0.05-1); and / or, The mass ratio of the monomer of the hydrophilic lubricating hydrogel coating to the surface grafting agent is 1:(0.05-100); preferably 1:(0.05-1).
5. The angiographic catheter with a hydrophilic lubricating coating as claimed in claim 1, characterized in that : The catheter surface is coated with a hydrophilic lubricating coating using a pre-impregnation process; The swelling process time is 1 to 60 minutes; preferably 1 to 5 minutes; and / or, The pre-impregnation process time is 1 to 60 minutes; preferably 1 to 5 minutes; and / or, The ultraviolet irradiation process time is 1 to 60 minutes, preferably 1 to 5 minutes.
6. The angiographic catheter with a hydrophilic lubricating coating as claimed in claim 1, characterized in that: The catheter seat is a hollow structure, having a catheter seat inlet and a catheter seat outlet, the catheter seat inlet is connected to the outside, the tube body and the catheter seat are connected through the catheter seat outlet, and there are two leaf pieces perpendicular to the outer surface of the catheter seat at opposite positions on the side of the catheter seat; and / or, The tube body comprises an inner tube layer, an intermediate braided tube layer and an outer tube layer; and / or, The transition section comprises a transition section inner layer and a transition section outer layer; and / or, The hardness of the tube body, transition section and guide head end decreases in sequence; The Shore hardness of the outer layer of the tube body is 50-70D; and / or, The Shore hardness of the outer layer of the transition section is 40-60D; and / or, The Shore hardness of the guide head end is 20-40D.
7. The angiographic catheter with a hydrophilic lubricating coating as claimed in claim 6, characterized in that : The catheter seat is made by injection molding or extrusion molding; and / or, The inner and outer layers of the tube body are both made by injection or extrusion; and / or, The middle braided layer of the tube body is made by machine braiding technology; and / or, The inner and outer layers of the transition section are both made by injection molding or extrusion molding; and / or, The intermediate braided layer of the transition section is made by machine braiding technology; and / or, The guide tip is manufactured by injection molding, extrusion molding or 3D printing; and / or The tube body and the catheter seat are connected by bonding, injection molding or welding; and / or The pipe body, the transition section and the guide head end are connected by injection molding or welding.
8. The angiographic catheter with a hydrophilic lubricating coating as claimed in claim 6, characterized in that : The catheter seat is made of acrylonitrile-butadiene-styrene terpolymer (ABS), polycarbonate (PC) or nylon 12; and / or, The inner layer of the tube body is made of polytetrafluoroethylene, nylon 12 or block polyether amide elastomer material; and / or The middle braided layer of the tube body is made of stainless steel; preferably made of 10 to 30 stainless steel round wires or flat wires, with a braiding density of 50 to 80 PPI; the stainless steel is SUS304 or SUS316; and / or The outer layer of the tube body is made of at least one of block polyetheramide elastomer (PEBAX), nylon, thermoplastic polyurethane, polyimide, styrene thermoplastic elastomer, acrylonitrile-butadiene-styrene terpolymer, and thermoplastic silicone elastomer; and / or, The inner layer of the transition section is made of polytetrafluoroethylene, nylon 12 or block polyether amide elastomer material: and / or, The intermediate braided layer of the transition section is made of stainless steel; preferably, it is made of 10 to 30 stainless steel round wires or flat wires, with a braiding density of 70 to 100 PPI; the stainless steel is SUS304 or SUS316; and / or, The outer layer of the transition section is made of at least one of block polyetheramide elastomer, nylon, thermoplastic polyurethane, polyimide, styrene thermoplastic elastomer, acrylonitrile-butadiene-styrene terpolymer, and thermoplastic silicone elastomer; and / or, The guide head end is made of at least one of block polyether amide elastomer, nylon, thermoplastic polyurethane, polyimide, styrene thermoplastic elastomer, acrylonitrile-butadiene-styrene terpolymer, and thermoplastic silicone elastomer.
9. The angiographic catheter with a hydrophilic lubricating coating as claimed in claim 8, characterized in that : The angiography catheter tip end of the hydrophilic lubricating coating has a developing ring having a guiding function under X-ray irradiation; and / or, The X-ray developing ring is at least one of a platinum-iridium alloy, a tantalum alloy, and rubber; preferably a platinum-iridium alloy.
10. Use of the angiography catheter with a hydrophilic lubricating coating as claimed in any one of claims 1 to 9 in cardiovascular and cerebrovascular angiography.
Citation Information
Cited By
Hydrophilic coating angiographic catheter and intelligent lubricant release system thereof
CN120437463A
A hydrophilic coating angiographic catheter and its lubricant smart release system
CN120437463B
Radial artery approach radiography cannula
CN121668511A
